Prevalência da infecção oral por HPV e associação dos polimorfismos GST em pacientes HIV positivos - Trevisan, Marcela Gonçalves (2022)
Human papillomavirus (HPV) infection is widely found in different population groups. However, in the face of immunosuppression, it can manifest as a clinical disease and progress to cancer. Currently, the growing increase in oropharyngeal squamous cell carcinomas associated with HPV is notorious, and Brazil is among the countries with the highest incidence of malignant tumors of the oral cavity. Nevertheless, genetic polymorphisms in glutathione-S-transferase (GST) enzymes also contribute to tumor risk, worse pathological outcomes, and viral infections, including human immunodeficiency virus (HIV) and HPV. However, scientific evidence indicates that deletion of the GSTM1 and GSTT1 genes may be related to normal counts of CD4+ T lymphocytes in HIV patients, reducing the progression of the disease. Therefore, the objective of the study was to verify the prevalence of oral HPV infection in HIV-positive patients linked to a Specialized Assistance Service in Southwest Paraná and the association of GSTM1 and GSTT1 polymorphisms with HIV viral infection. The quantitative approach research was carried out between 2020 and 2022 in a Specialized Care Service in the Southwest of Paraná. Sampling was for convenience, using a closed questionnaire with sociodemographic, behavioral and clinical variables. Oral mucosa samples were collected by the researchers themselves for detection of HPV and GSTM1 and GSTT1 polymorphisms, respectively, via simple and multiplex PCR (Polymerase Chain Reaction). Data received descriptive statistical treatment including HPV prevalence and associations between genetic polymorphisms and HIV viral infection. Pearson Chi-square (X2) test was used for categorical variables, with results with p<0.02 and logistic regression with a significance of 95% and a confidence interval (CI) of 95% being considered significant. The results showed a prevalence of only 2,3% of HPV in the oral mucosa of individuals with HIV and no sociodemographic, behavioral and lifestyle correlates were identified. However, among the 4 carriers of oral HPV, 3 were male and 1 female. There was a predominance of heterosexual patients, not immunized, with more than 5 sexual partners in life, and 75% of them practice oral sex without protection. With regard to HIV infection, a higher frequency of white, married, low-education women was found, with sexual intercourse as the main form of viral transmission. Regarding genotypic frequencies, GST nullity was high in the population, being 97.5% and 97.6%, respectively. Although, we identified the lack of association between the GST polymorphism and the viral load and CD4+ T lymphocyte count at diagnosis, when related to the current CD4+ count, the isolated and combined null alleles, GSTT1 (ORadj: 0.219; p=0.004 ), GSTM1 (ORadj: 0.219; p=0.004), GSTM1/T1 (ORadj: 0.219; p=0.004) were defined as favorable factors for a minimum CD4+ T cell count of 350 cells/mm3.